The meanings of prenatal assigned by pregnant women performed by nurses (Research, Society and Development, 2021)
Introduction: Prenatal care should be based on the quality of care, comprehensiveness and humanization for health promotion, prevention of diseases or injuries and recovery of maternal and neonatal health. The valorization of the woman's opinion about the decisions that involve her therapeutic plan is relevant and timely; therefore, this article aims to understand the meanings attributed by pregnant women to the prenatal care performed by nurses. Methodology: This is an exploratory, descriptive study, with a qualitative approach, with twelve pregnant women registered in a Family Health Strategy program in the northern region of the state of Mato Grosso, Brazil. Data collection took place through semi-structured interviews, analyzed according to thematic content analysis. Results: two thematic categories emerged from the findings: a) giving meaning to the gestational period and prenatal care; and b) the quality of the prenatal nursing consultation. Conclusion: the results suggest that the prenatal care performed by a nurse and the importance of the prenatal care quality were considered as an important and necessary process. The women felt motivated by the nurses’ care and attention in the consultations, especially when the professionals clarified the women’s doubts. In addition, it fosters the discussion on nursing entrepreneurship initiatives and the strengthening of the professional category and professional identity, which have been constant in the various health services.